Endoscopic third ventriculostomy - Yadav, Yad Ram (Medknow Publications & Media Pvt Ltd, 2012)
Endoscopic third ventriculostomy (ETV) is considered as a treatment of choice for obstructive hydrocephalus. It is indicated in hydrocephalus secondary to congenital aqueductal stenosis, posterior third ventricle tumor, cerebellar infarct, Dandy-Walker malformation, vein of Galen aneurism, syringomyelia with or without Chiari malformation type I, intraventricular hematoma, post infective, normal pressure hydrocephalus, myelomeningocele, multiloculated hydrocephalus, encephalocele, posterior fossa tumor and craniosynostosis. It is also indicated in block shunt or slit ventricle syndrome. Proper Pre-operative imaging for detailed assessment of the posterior communicating arteries distance from mid line, presence or absence of Liliequist membrane or other membranes, located in the prepontine cistern is useful. Measurement of lumbar elastance and resistance can predict patency of cranial subarachnoid space and complex hydrocephalus, which decides an ultimate outcome. Water jet dissection is an effective technique of ETV in thick floor. Ultrasonic contact probe can be useful in selected patients. Intra-operative ventriculo-stomography could help in confirming the adequacy of endoscopic procedure, thereby facilitating the need for shunt. Intraoperative observations of the patent aqueduct and prepontine cistern scarring are predictors of the risk of ETV failure. Such patients may be considered for shunt surgery. Magnetic resonance ventriculography and cine phase contrast magnetic resonance imaging are effective in assessing subarachnoid space and stoma patency after ETV. Proper case selection, post-operative care including monitoring of ICP and need for external ventricular drain, repeated lumbar puncture and CSF drainage, Ommaya reservoir in selected patients could help to increase success rate and reduce complications. Most of the complications develop in an early post-operative, but fatal complications can develop late which indicate an importance of long term follow up.